A Conductance-Based MPPT Method with Reduced Impact of the Voltage Ripple for One-Phase Solar Powered Vehicle or Aircraft Systems - Tomasz Binkowski (Energies, 2020)
This paper presents a novel maximum power point tracking method for photovoltaic inverters with a single phase connection to the onboard 400Hz vehicle or aircraft grid, supplying drives operating in a critical mode. By taking into account that the power fluctuations cause voltage ripples at the termini of photovoltaic panels connected to the DC-link capacitor, this paper proposes a conductance base maximum power point tracking method. The impact of varying voltage has been reduced to ensure the constant reference current for the grid current calculation problem, which has been reported in previous studies. Accordingly, a conductance base tracking method, grid current control, is proposed and implemented to ensure the expected output current with respect to varying power. As described in this paper, the exemplified solar converter prototype can implement constant reference photovoltaic current control with a maximum power point achievement under continuous voltage rippling. Experimental results are given to verify the feasibility of the proposed MPPT method, which significantly improves the power efficiency for solar powered vehicles or aircraft.